2024
DOI: 10.1002/cjoc.202400145
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis of a Key Precursor Relevant to the Tetrasaccharide Repeating Unit from Treponema mediumATCC 700293

Wenbin Sun,
Guangzong Tian,
Meiru Ding
et al.

Abstract: Comprehensive SummaryTreponema is a Gram‐negative anaerobic bacterium, among which the pathogenic Treponema can cause various diseases, such as venereal syphilis (Treponema pallidum), yaws (Treponema carateum), and oral diseases (Treponema denticola and Treponema medium). Although different from conventional lipopolysaccharides, the extracellular glycoconjugate of Treponema may still be a potential antigen and provide a candidate for vaccine development. Hence, we completed the first chemical synthesis of Trep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…9 To avoid the challenge of controlling chemoselectivity in subsequent 3-O-protection, a novel orthogonal protection strategy (Scheme 2) was employed, starting from known Dglucosamine 5. 16 Selective monotosylation of 5 using 4toluenesulfonyl chloride (TsCl) yielded desired 6-O-tosyl derivative 6 in 91% yield. Subsequent reduction with lithium aluminum hydride failed to provide the desired product but caused degradation of compound 6, possibly due to incompatibility with the NHTCA group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 To avoid the challenge of controlling chemoselectivity in subsequent 3-O-protection, a novel orthogonal protection strategy (Scheme 2) was employed, starting from known Dglucosamine 5. 16 Selective monotosylation of 5 using 4toluenesulfonyl chloride (TsCl) yielded desired 6-O-tosyl derivative 6 in 91% yield. Subsequent reduction with lithium aluminum hydride failed to provide the desired product but caused degradation of compound 6, possibly due to incompatibility with the NHTCA group.…”
mentioning
confidence: 99%
“…Recently, Mulard et al reported a synthesis of AAT from d -glucosamine, which similarly utilized the NHTCA group or dichloroacetamido (NHDCA) group to mask the acetamido group and placed the key C6 deoxygenation step at an early stage . To avoid the challenge of controlling chemoselectivity in subsequent 3- O -protection, a novel orthogonal protection strategy (Scheme ) was employed, starting from known d -glucosamine 5 . Selective monotosylation of 5 using 4-toluenesulfonyl chloride (TsCl) yielded desired 6- O -tosyl derivative 6 in 91% yield.…”
mentioning
confidence: 99%